Ophthalmomyiasis externa - El mhadi, Mohcine; El ouafi, Aziz (Digital Journal of Ophthalmology, 2023)
A 25-year-old military man presented at the Ophthalmology Department, Military Hospital Moulay Ismail of Meknes, for evaluation of a red, painful right eye, with mobile foreign body sensation 2 hours after eye contact with a fly. On examination, his best-corrected visual acuity was 20/20 in each eye. Slit-lamp examination of the right eye revealed 12 larvae of Oestrus ovis (A), each about 1 mm in length, translucent and with blackish anterior hooks (B), photophobic, and predominantly in the internal and external conjunctival fornices. The rest of the examination was unremarkable. Extraction of the larvae was performed under topical anesthesia using forceps and completed with saline eye wash and treatment with antibiotic and corticosteroid eye drops, with complete improvement after 48 hours. Ophthalmomyiasis externa is a benign condition if treated early. Rapid diagnosis and complete extraction can prevent intraocular penetration of the larvae, which can lead to blindness.